2017
DOI: 10.1136/bmjopen-2016-014548
|View full text |Cite
|
Sign up to set email alerts
|

Social and somatic determinants of underweight, overweight and obesity at 5 years of age: a Norwegian regional cohort study

Abstract: ObjectiveTo identify associations between the weight groups underweight (UW), overweight (OW) and obesity (OB) at 5 years of age and exposures related to pregnancy, anthropometric measures at birth, sociodemographic factors, and family health, anthropometric measures and habits.DesignRegional cohort study.SettingOppland County, Norway.MethodsPregnancy data were obtained from a prospective perinatal register for children born in the county, and weight and height were measured by midwives at birth and by public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
1
21
1
4
Order By: Relevance
“…Notably, a recent large cohort study (not yet included in any of the meta-analyses) showed that after adjustment for several confounding factors, obesity was only marginally related to dietary patterns and unrelated to physical activity, while low parental education was associated with childhood obesity. 22 Large-scale epidemiological data also seem to support this finding. Although it is presumed that the urbanization of society has significantly contributed to the emergence of the obesity epidemic, for example, due to a lack of opportunities for the practice of physical activity, a large-scale analysis of the health effects of obesity in 195 countries over 25 years noted that alarming rates of obesity took place well before urbanization across several cultures.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Notably, a recent large cohort study (not yet included in any of the meta-analyses) showed that after adjustment for several confounding factors, obesity was only marginally related to dietary patterns and unrelated to physical activity, while low parental education was associated with childhood obesity. 22 Large-scale epidemiological data also seem to support this finding. Although it is presumed that the urbanization of society has significantly contributed to the emergence of the obesity epidemic, for example, due to a lack of opportunities for the practice of physical activity, a large-scale analysis of the health effects of obesity in 195 countries over 25 years noted that alarming rates of obesity took place well before urbanization across several cultures.…”
Section: Comparison With Other Studiesmentioning
confidence: 84%
“…To the best of our knowledge, no other umbrella review has graded evidence from meta‐analyses of putative environmental risk factors for obesity as well as evidence from randomized controlled nonpharmacological and nonsurgical interventions both in adults and children, including only patients affected by obesity and excluding overweight participants. Notably, a recent large cohort study (not yet included in any of the meta‐analyses) showed that after adjustment for several confounding factors, obesity was only marginally related to dietary patterns and unrelated to physical activity, while low parental education was associated with childhood obesity . Large‐scale epidemiological data also seem to support this finding.…”
Section: Discussionmentioning
confidence: 96%
“…From this cohort, we have previously reported that exclusive breastfeeding for at least 4 months was not significantly associated with a risk of overweight and obesity at pre‐school age . The present study adds that there were no significant effects on BMI or risk of overweight or obesity in the third grade, an age at which children are becoming more independent.…”
Section: Discussionmentioning
confidence: 99%
“…Наличие такой связи сложно опосредуется взаимодействием генетических факторов с факторами семейного окружения, формирующими так называемое обесогенное поведение ребенка: низкая физическая активность, длительное экранное время, нездоровые паттерны питания, короткая продолжительность сна. Как интересную находку нашего исследования следует отметить то, что мы, в отличие от большинства других исследователей, показавших связь избыточного веса детей с весом обоих родителей [10,11], обнаружили, что ожирение у сельских подростков связано с ИМТ их матерей, но не отцов. Результаты, сходные с полученными нами, были получены еще в двух исследованиях, в которых, к сожалению, не приведены данные о территории проживания включенных в выборку детей [7,9].…”
Section: обсуждение основного результата исследованияunclassified
“…Результаты, сходные с полученными нами, были получены еще в двух исследованиях, в которых, к сожалению, не приведены данные о территории проживания включенных в выборку детей [7,9]. И еще в одном исследовании, хотя и была установлена связь ожирения ребенка с ИМТ отца, подчеркивалось, что ИМТ матери влияет на вес ребенка значительно сильнее [11]. Можно предположить, что показанная нами ассоциация во многом реализуется через преимущественную роль матери в формировании семейной среды в сельских общинах, которая, в свою очередь, определяет паттерны питания и образа жизни ребенка.…”
Section: обсуждение основного результата исследованияunclassified